In-beam spectroscopic studies of shape coexistence and collectivity in the neutron-deficient Z ≈ 82 nuclei. (14th January 2016) - Julin, R; Grahn, T; Pakarinen, J; Rahkila, P
Abstract: In the present paper we focus on studies of shape coexistence in even-mass nuclei in the neutron-deficient Pb region. They are based on experiments carried out using tagging techniques in the Accelerator Laboratory of the University of Jyväskylä, Finland. Excited states in many of these nuclei can only be accessed via fusion-evaporation reactions employing high-intensity stable-ion beams. The key features in these experiments are high selectivity, clean spectra and instrumentation that enables high count rates. We review three spectroscopic highlights in this region.